Konsep Hukum Pidana dalam Al-Qur'an - Husnawadi, Husnawadi (Al-aqidah | Jurnal Studi Islam, 2018)
Many criminal acts have not received the appropriate penalties. the law has not been able to provide the best solution to the criminal act. This paper wants to focus on the concept of criminal law in the Qur?an, as a universal concept for the benefit of mankind. The concept of Islamic criminal law is used as a legal basis to overcome various crimes against humanity. The law serves to guide the conduct of individuals, their relationships with others, and their actions in Islamic societies or beyond. The thematic method is chosen as an analysis knife to examine the problem.